KECERDASAN SPIRITUAL DALAM PRESTASI KERJA KARYAWAN (IAIN Tulungagung, 2019)
This study aims to determine the effect of work environment, spiritual intelligence and workload on employee performance at University of Muhammadiyah Malang alumni class of 2007 faculty of economics and business management majors. The results showed that the work performance of employees by University of Muhammadiyah Malang alumni in the year 2007 of the Economics and Business faculties majoring in management was influenced by the spiritual intelligence of each individual, while the work environment and workload had no effect. This is due to high spiritual intelligence that will make individuals have more meaning in addressing work and things that will be received by employees in the future. This study uses multiple linear regression analysis using primary data collected through social media whatsapp.